Answers

2015-02-16T20:51:59+05:30
Let one no=x
other no=x+6
accrdng to the statement..
x(x+6)=72
i.e x2(x square)+6x-72=0
 using the method splitting the middle term...
x2+6x-72=0
x2+12x-6x-72=0
takng common terms..
x(x+12-6()x+12)=0
i.e (x+12)(x-6)=0
i.e (x+12)=0 or (x-6)=0
therefor,.. x= -12 or 6
as value cannot be negative,we take the +ve value i.e 6
so x=6
substitute these values in the place of x
one no=x=6
and other no=x+6
                    =6+6=12
and sum of these 2 nos=6+12
                                     =18

u can even verify the answer
as gvn theirproduct is 72
i.e 6*12=72

so we got the ri8  answer......:)


0
2015-02-16T21:29:06+05:30
Let the one number be x and second be y.

x - y = 6
x = 6 +y ======(1)

xy = 72
(6 + y)y = 72          [ FROM 1 ]
6y + y² = 72
y² + 6y - 72 = 0
y² + 12y - 6y - 72 = 0
y(y + 12 ) - 6(y +12)
(y - 6)(y + 12)
y = 6 or y = - 12 [REJECTED]

The value of y is 6 then the value of x = 
x = 6 + 6 = 12

Now the sum of both the numbers is 12 + 6 = 18
0